PENGARUH KEPEMILIKAN SAHAM DAN RASIO KEUANGAN TERHADAP STRUKTUR MODAL PERUSAHAAN - Lestari, Sisil Ayu; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the influence of stock ownership and financial ratio to the company capital structure on the manufacturing companies in 2010-2013 periods which are listed in Indonesia Stock Exchange. The sample has been done by using purposive sampling method and 236 annual financial statements of 78 manufacturing companies which have published their statement through official sites of Indonesia Exchange (www.idx.co.id). The test has been conducted by using multiple regressions analysis with the support of SPSS (Statistical Package for Social Sciences) 20 version, with the independent variables which are: the majority of stockholders (the ownership of stock > 5% is divided by shares in circulation), public stockholders (the logarithm of the number of ownership of stocks < 5%), the dividend policy (dividend payout ratio), free cash flow (the remaining of the subtraction of operating cash flow, capital expenditures and net working capital), profitability (return on asset), firm size (natural logarithm of the total asset) and business risk (return on invested capital) to the dependent variable which is the company capital structure (debt equity ratio). The result of the research shows that 5 variables have influence and 2 variables do not have any influence to the company capital structure. Five variables which have influence to the company capital structure consist of 4 variables which have negative and significant which includes the majority of stockholders, public stockholders, dividend policy, and business risk. Meanwhile, 1 variable which has significant and positive influence is free cash flow. Two variables which do not have any influence to the company capital structure are profitability and firm size. Keywords: Majority Stockholders, Public Stockholders, Financial Ratio, Capital Structure and Multiple Regressions.